Frequency and structures of lexical bundles in the German Goethe-Institut website - Ayuni, Amalia Qurrota; Yuliawati, Susi; Ekawati, Dian (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2022)
Corpus linguistics allows researchers to discover the nature of language use through lexical bundles throughout genres, registers, and language varieties. With the fast-changing development of the internet, the language of websites has become one fascinating variety to investigate. In the contexts of German language studies, Goethe-Institut is a worldwide German cultural institution dedicated to teaching German and propagating German culture, with its website becoming a well-known source for German-related studies. Under these considerations, this research is interested in analyzing the German language patterns in Goethe-Institut website by examining their frequency and structure of lexical bundles. Using a mixed-method approach, the corpus was found to be dominated by lexical bundles within the ranges of three- and four-bundles, with the least quantity of lexical bundles in the range of five. The majority of the four-word lexical bundles on this site fell into the categories of noun, preposition, or verb groups. Meanwhile, the adverb, conjunction, and adjective groups were the fewest to appear in the four-word lexical bundles. The language in the Goethe-Institut was shown to contain semi-formal expressions according to the frequency of use of the prepositions, nouns, verbs, and the active sentence expressions. The utilization of standardized German language and basic vocabulary indicates that this website is designed to be accessible for everyone, including German language learners. The language usage also demonstrates that the Goethe-Institut is especially a user-oriented website with expressions that evoke a